AI-Driven Data Governance for AML/KYC in Credit Card Issuance: A Framework to Reduce Regulatory Consent Orders - Sanjay Chandrakant Vichare (International Journal of Computational and Experimental Science and Engineering, 2025)
In the very digitalized financial world today, the convergence of artificial intelligence (AI) and data governance can transform anti-money laundering (AML) and know-your-customer (KYC) compliance in credit card issuing. This paper discusses how AI-governance models can assistin closing regulatory gaps, enhance operational performance, and reduce the likelihood of regulatory consent orders. Based on current research and AML/KYC industry applications, the paper determines the most common AI techniques in AML/KYC to include machine learning, natural language processing, and explainable AI.